All Days 2010
DOI: 10.2118/127783-ms
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Behavior of a Fissured Dual-Carbonate Reservoir Modeled with DFN

Abstract: A Paleocene dolomite in northeastern Libya was modeled using three porosity types: matrix porosity (intercrystalline plus the separate vugs), horizontal-to-subhorizontal solution-enlarged vuggy porosity generated by dissolution and named "touching vugs," and fracture porosity.The touching vugs, which acted like fractures in their dynamic behavior, are modeled as a very permeable discrete fracture network (DFN) in PETREL* seismic-to-simulation software. Their presence is known primarily due to pressure buildup … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 8 publications
0
0
0
Order By: Relevance
“…Additionally, pressure drop and recovery factor in the reservoir are influenced by it [27]. Touching vugs, observed when fracturing decrease, are important because they can increase production [28]. Gomaa and co-authors added two definitions of vugs: (i) pores of throats of diameters >5 microns, observed in the mercury injection capillary pressure experiments, and (ii) pores, filled with water or light oil, larger than approximately 50 microns, observed in the NMR log outcomes [29].…”
Section: Porositymentioning
confidence: 99%
“…Additionally, pressure drop and recovery factor in the reservoir are influenced by it [27]. Touching vugs, observed when fracturing decrease, are important because they can increase production [28]. Gomaa and co-authors added two definitions of vugs: (i) pores of throats of diameters >5 microns, observed in the mercury injection capillary pressure experiments, and (ii) pores, filled with water or light oil, larger than approximately 50 microns, observed in the NMR log outcomes [29].…”
Section: Porositymentioning
confidence: 99%
“…The term "carbon" in this paper refers to "carbon dioxide". However, due to the existence of a vuggy system that produces intricate matrixfracture interactions in carbonate reservoirs, simulating a reasonable fracture network and its connectivity in naturally fractured carbonate reservoirs remains a challenge for researchers [9][10][11][12]. Other issues include the magnitude and resolution of the fractures applied in the modelling.…”
Section: Introductionmentioning
confidence: 99%